HUBUNGAN KONDISI LINGKUNGAN FISIK RUMAH DENGAN KEJADIAN PNEUMONIA PADA BALITA DI WILAYAH KERJA PUSKESMAS JATIBARANG KABUPATEN INDRAMAYU - Corry Wahyuni Hidayat; Suhartono Suhartono; Dharminto Dharminto (Jurnal Kesehatan Masyarakat (Undip), 2016)
Pneumonia still becomes a public health problems that causing pain and death on children, so that towards the older persons. In 2014 found 14.019 cases of Pneumonia that took place in Indramayu. This Pneumonia syndrome mostly happened and even takes a high rank of disease that attacks Jatibarang territory, which found 1.116 cases. The main goals of this observation is to analyze the correlation between house environment physically with the Pneumonia that  involved children under five at Puskesmas (Public Health Centre) in Jatibarang Teritory, Indramayu. This observation is using Retrospective Study methode, Case – Control methode. Case group involved 38 respondents, and Control group 38 respondents. Whilst, Data Analysis is using Univariat and Bivariat analysis with Chi Square. And Risk Variable is using Odds Ratio. The result shows from 8 Independent variables analysis there are 2 variables that related to Ventilation Width (p-value= 0,004 OR=9,360) and the existences of chimney (p-value= 0,028 OR=6,429). The conclusion of this observation is there certainly any correlation between Housing Ventilation Width and Chimney towards the Pneumonia that involved the children under five. Hopefully, should be increased behavior to open ventilation which are home that the exchange of air circulation.